Clinical Features and Imaging Findings of Myelin Oligodendrocyte Glycoprotein-IgG-Associated Disorder (MOGAD) - Li, Yunjie; Liu, Xia; Wang, Jingxuan; Pan, Chao; Tang, Zhouping (Frontiers in Aging Neuroscience, 2022)
Myelin oligodendrocyte glycoprotein-IgG-associated disorder (MOGAD) is a nervous system (NS) demyelination disease and a newly recognized distinct disease complicated with various diseases or symptoms; however, MOGAD was once considered a subset of neuromyelitis optica spectrum disorder (NMOSD). The detection of MOG-IgG has been greatly improved by the cell-based assay test method. In one study, 31% of NMOSD patients with negative aquaporin-4 (AQP-4) antibody were MOG-IgG positive. MOGAD occurs in approximately the fourth decade of a person’s life without a markedly female predominance. Usually, optic neuritis (ON), myelitis or acute disseminated encephalomyelitis (ADEM) encephalitis are the typical symptoms of MOGAD. MOG-IgG have been found in patients with peripheral neuropathy, teratoma, COVID-19 pneumonia, etc. Some studies have revealed the presence of brainstem lesions, encephalopathy or cortical encephalitis. Attention should be given to screening patients with atypical symptoms. Compared to NMOSD, MOGAD generally responds well to immunotherapy and has a good functional prognosis. Approximately 44-83% of patients undergo relapsing episodes within 8 months, which mostly involve the optic nerve, and persistently observed MOG-IgG and severe clinical performance may indicate a polyphasic course of illness. Currently, there is a lack of clinical randomized controlled trials on the treatment and prognosis of MOGAD. The purpose of this review is to discuss the clinical manifestations, imaging features, outcomes and prognosis of MOGAD.